Design Criteria for AI-Generated Logos - Munoz-Baldi, A (UNIV VIC, 2025)
Artificial intelligence, as a tool for generating logos, is transforming the field of brand design, making it necessary to review new ways of evaluating the outcomes it produces. This study conducts a descriptive-comparative analysis, using a comparative matrix of the main design criteria as a measurement instrument, while providing background elements that should be considered for prompt writing. As a result of this analysis, the study highlights the analytical role required from the user in assessing the quality of the outputs produced by generative artificial intelligence (GenAI).